2016
DOI: 10.1007/s00586-016-4414-7
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical and radiographic 12-month outcome study of patients undergoing single-level anterior cervical discectomy and fusion for symptomatic cervical degenerative disc disease utilizing a novel viable allogeneic, cancellous, bone matrix (trinity evolution™) with a comparison to historical controls

Abstract: Purpose This multicenter clinical study was performed to assess the safety and effectiveness of Trinity Evolution Ò (TE), a viable cellular bone allograft, in combination with a PEEK interbody spacer and supplemental anterior fixation in patients undergoing anterior cervical discectomy and fusion (ACDF). Methods In a prospective, multi-center study, 31 patients that presented with symptomatic cervical degeneration at one vertebral level underwent ACDF with a PEEK interbody spacer (Orthofix, Inc., Lewisville, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…For the interspinous process method, no motion (9 of 22, 40.9%) [ 13 , 14 , 17 , 21 , 24 , 26 , 29 , 33 , 37 ], under 1 millimeter (mm) (7 of 22, 31.8%) [ 10 , 20 , 28 , 31 , 32 , 41 , 42 ], under 2 mm (2 of 22, 9.1%) [ 12 , 35 ], and under 3 mm of motion (4 of 22, 18.2%) [ 27 , 30 , 40 , 43 ] between spinous process were all used as cutoff values for a definition of fusion. Using the Cobb angle method, changes of 1 degree (1 of 12, 8.3%) [ 38 ], 1.5 degrees (1 of 12, 8.3%) [ 42 ], 2 degrees (5 of 12, 41.7%) [ 19 , 25 , 36 , 44 , 46 ], 4 degrees (4 of 12, 25.0%) [ 11 , 43 , 45 ], and 5 degrees (2 of 12, 16.7%) [ 27 , 30 ] were all used in various studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the interspinous process method, no motion (9 of 22, 40.9%) [ 13 , 14 , 17 , 21 , 24 , 26 , 29 , 33 , 37 ], under 1 millimeter (mm) (7 of 22, 31.8%) [ 10 , 20 , 28 , 31 , 32 , 41 , 42 ], under 2 mm (2 of 22, 9.1%) [ 12 , 35 ], and under 3 mm of motion (4 of 22, 18.2%) [ 27 , 30 , 40 , 43 ] between spinous process were all used as cutoff values for a definition of fusion. Using the Cobb angle method, changes of 1 degree (1 of 12, 8.3%) [ 38 ], 1.5 degrees (1 of 12, 8.3%) [ 42 ], 2 degrees (5 of 12, 41.7%) [ 19 , 25 , 36 , 44 , 46 ], 4 degrees (4 of 12, 25.0%) [ 11 , 43 , 45 ], and 5 degrees (2 of 12, 16.7%) [ 27 , 30 ] were all used in various studies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to plain radiographs, CT scans were frequently used (53.8%) [ 10 , 12 , 15 , 16 , 19 , 22 , 26 , 29 , 33 - 38 , 41 , 43 , 45 - 49 ], to assess pseudoarthrosis following ambiguous radiographic findings. The interobserver reliability of predicting pseudoarthrosis is better using the CT scan despite the metal artifacts compared to dynamic cervical spine films [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…They generally report fusion rates 90% or greater at the 12 or 24 month point using a combination of plain films and computed tomography scans. A recent multicenter study looking at patients with 12 months of follow-up after undergoing single level ACDF with a commercial CBM product noted an overall fusion rate of 93.5% that persisted even when stratifying for patients with high risk factors (history of smoking, diabetes, obesity/severe obesity) [29]. In our study, patients underwent multilevel fusion and only 5 out of the 21 patients had no medical risk factors for adverse outcomes.…”
Section: Discussionmentioning
confidence: 61%
“…Studies have shown that low-profile PEEK cages may reduce esophageal damage because its placement is limited to the confinement of the intervertebral disc space. Other types of newer cages, such as hybrid cages that combine PEEK and titanium, need more clinical evidence to fully understand their efficacy and long-term safety [ 27 ].…”
Section: Reviewmentioning
confidence: 99%